COSTS OF LAND ACQUISITION: FEATURES OF TAX ACCOUNTING - Lyubov A. Mironova (Статистика и экономика, 2016)
The article considers the main features of tax accounting of costs for land acquisition, the main difficulties that might arise. It also analyzes the current legislation and the present judicial positions on evidence of the purposes of capital construction in the purchase of such lands and particularities of obtaining the status of capital facilities of real estate.